Analisis Komparatif Minat, Motivasi, dan Hasil Belajar Biologi dengan Model Problem Based Learning dan Cooperative Learning Tipe STAD - Akida Akida; Yusminah Hala; Syamsiah Syamsiah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Copyright©2023 The low interest and motivation in learning that students have during the learning process can be seen by the lack of participation of students in expressing their opinions it affects the learning outcomes of the students themselves. This study aimed to determine the differences in interest, motivation, and learning outcomes of students through the PBL model and the STAD-type Cooperative Learning model. This research was a quasi-experimental study using a pretest-posttest control group design. The sample in this study were students of class XI MIPA taught using the PBL model and the STAD-type Cooperative Learning model. Data collection was carried out by filling out interest, motivation, and learning achievement tests twice, namely the pre-test and post-test. Data analysis was carried out descriptively in the form of N-Gain measurements of normality and inferentially in the form of Normality tests, Homogeneity tests, and independent sample t-Test Hypothesis Tests using the SPSS version 24 system. From the results of this study, it concludes that there are significant differences in interest, motivation, and learning outcomes of students with the application of the PBL learning model and the STAD-type Cooperative Learning model, where the application of the PBL model shows a higher post-test average value than the post-test average value of the STAD Cooperative Learning model so that the PBL model is more effective for use in increasing the interest, motivation, and learning outcomes of students.